Competing in Hot Conditions at the Tokyo Olympic Games: Preparation Strategies Used by Australian Race Walkers - Carr, Amelia J.; Vallance, Brent S.; Rothwell, Jessica; Rea, Anna E.; Burke, Louise M.; Guy, Joshua H. (Frontiers in Physiology, 2022)
Introduction: The Tokyo 2021 Olympic Games was anticipated to expose athletes to the most challenging climatic conditions experienced in the history of the modern Olympic Games. This observational case study documents strategies executed by Australian endurance athletes during the team holding camp and Olympic Games experiences, including (1) baseline physiological data, training data, and heat acclimation/acclimatization practices; (2) pre- and in-race cooling and nutritional strategies, and (3) Olympic Games race performance data. Methods: Data were collected from the six Australian team race walking representatives (three male, three females; age 24 ± 4 years; VO2max 63.2 ± 8.7 mL·kg-1·min-1; sum of 7 skinfolds 53.1 ± 23.4 mm), prior to and during the team holding camp held in Cairns, Queensland, Australia. Race performance data and environmental conditions from the 2021 Olympic Games were also documented. Athletes completed 6-7 weeks of heat acclimation training, utilizing a combination of 2-4 passive and active acclimation sessions per week. Active acclimation was systematically increased via exposure time, exercise intensity, temperature, and humidity. In the team holding camp, athletes undertook a further 23 heat acclimatization training sessions over 18 days. Hyperhydration (using sodium and glycerol osmolytes), and internal and external pre-and in-race cooling methods were also utilized. A low energy availability intervention was implemented with two athletes, as a strategy to periodize ideal race body composition. Results: The highest values for aerobic capacity were 63.6 mL·kg-1·min-1 for female race walkers and 73.7 mL·kg-1·min-1 for males. Training volume for the six athletes was the highest in the second week of the team holding camp, and training intensity was lowest in the first week of the team holding camp. Performance outcomes included 6th place in the women’s 20 km event (1:30:39), which was within 2% of her 20 km personal best time, and 8th place in the men’s 50 km event (3:52:01), which was a personal best performance time. Conclusions: The periodized training, heat acclimation/acclimatization, cooling and nutritional strategies documented in this observational case study may benefit elite race walkers prior to and during major championship events held in hot, humid conditions.